Higher Order Thinking Laboratory (HOT Lab)-Based Physics Learning: A Systematic Literature Review - Mujib Ubaidillah; Putut Marwoto; Wiyanto Wiyanto; Bambang Subali (International Conference on Science, Education, and Technology, 2022)
This study aims to analyze physics learning based on HOT Laboratory. The research method uses a literature review. Data collection was based on the Scopus, DOAJ, IOP Science, and Google Scholar database sources. The types of documents come from journal articles and conference papers with the keywords "HOT-Laboratory", "HOT-Lab", "Higher order thinking laboratory" and "HOT Lab" from 2015-2021. Based on a search through Harzing's Publish or Perish with these keywords, 957 articles were found. Articles that are eligible and reviewed are 21 articles. The literature review used a procedure adapted from PRISMA. Published documents are checked based on pre-determined content analysis criteria involving a year of publication, author, article source, the topic of practicum material, research subject, HOT Laboratory model innovation. The results showed that the topic of physics material that is often used in research is electricity. The dependent variable that is often used for research on the HOT Laboratory model is critical thinking skills. Other dependent variables used creative thinking skills, problem-solving skills, decision-making skills, collaboration skills, and scientific communication. The HOT Laboratory model is mostly applied to prospective physics teacher students. The HOT real laboratory is a practicum model that is often used in research. The HOT real laboratory provides real experience and laboratory skills for students. The innovation of the HOT Laboratory model was developed into a HOT Virtual Laboratory based on considerations of effectiveness and efficiency, the development of ICT. The e-module-based HOT Laboratory is based on the easy accessibility of e-modules and the development of ICT. The HOT Laboratory model can be applied to material topics related to the student context, and to develop habits of minds.